2018
DOI: 10.1007/s00167-018-5257-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative range of motion and applications of continuous passive motion predict outcomes after knee arthroplasty in patients with arthritis

Abstract: Purpose This study evaluated the clinical efficacy of continuous passive motion (CPM) following knee arthroplasty and determined the predictors of effect sizes of range of motion (ROM) and functional outcomes in patients with knee arthritis. Methods A comprehensive electronic database search was performed for randomized controlled trials (RCTs), without publication year or language restrictions. The included RCTs were analyzed through meta-analysis and risk of bias assessment. Study methodological quality (MQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Because the mean preoperative ROM in the CG (81.8°) was lower than that in the EG (87.4°), the results indicated that preoperative ROM may influence total ROM restoration after TKR surgery. The results of this study are supported by those of our previous study, which have indicated that preoperative ROM affects knee flexion after TKR surgery [ 56 ]. From the perspective of the ICF classification system, the EG exhibited a higher odds ratio for treatment success than the CG for mobility of joint function (code b710), which affects knee ROM.…”
Section: Discussionsupporting
confidence: 89%
“…Because the mean preoperative ROM in the CG (81.8°) was lower than that in the EG (87.4°), the results indicated that preoperative ROM may influence total ROM restoration after TKR surgery. The results of this study are supported by those of our previous study, which have indicated that preoperative ROM affects knee flexion after TKR surgery [ 56 ]. From the perspective of the ICF classification system, the EG exhibited a higher odds ratio for treatment success than the CG for mobility of joint function (code b710), which affects knee ROM.…”
Section: Discussionsupporting
confidence: 89%
“…However, some studies nd different results to ours. McInnes et al [29] or Lenssen et al [30] described an increment in active exion on the earlier postoperative days, in patients who received CPM, but not long-term bene t. Liao et al [31] obtain an improvement on ROM at 3rd and 6th month follow-up with an early application of CPM with initial high exion angle and rapid progress.…”
Section: Discussionmentioning
confidence: 98%
“…But the use of CPM in the post-TKA has remained controversial. Several studies have reported bene ts of CPM during the acute phase [10,22,31,32], while others report the absence of bene ts [11,28,33]. But we should be careful and be prudent when comparing these different studies, because there is a high degree of heterogeneity in rehabilitation protocols, with different frequency and duration of CPM applied, anesthetic and analgesic drugs used, among other.…”
Section: Discussionmentioning
confidence: 99%
“…Naylor et al reported that greater knee ROM at discharge after TKR was a significant predictor of improved ROM after rehabilitation [13]. A recent meta-analysis provided statistically significant, moderate evidence, indicating that CPM reduced pain, restored knee ROM and enhanced functional recovery after TKR regardless of follow-up duration [14]. It has been suggested that CPM leads to positive biological effects on tissue healing, oedema and haemarthrosis [11,15].…”
Section: Continuous Passive Motion (Cpm)mentioning
confidence: 99%